Novel perspectives on the therapeutic role of cryptotanshinone in the management of stem cell behaviors for high-incidence diseases - Guo, Xiaomeng; Ma, Ruishuang; Wang, Meng; Wui-Man Lau, Benson; Chen, Xiaopeng; Li, Yue (Frontiers in Pharmacology, 2022)
Cryptotanshinone (CTS), a diterpenoid quinone, is found mostly in Salvia miltiorrhiza Bunge (S. miltiorrhiza) and plays a crucial role in many cellular processes, such as cell proliferation/self-renewal, differentiation and apoptosis. In particular, CTS's profound physiological impact on various stem cell populations and their maintenance and fate determination could improve the efficiency and accuracy of stem cell therapy for high-incidence disease. However, as much promise CTS holds, these CTS-mediated processes are complex and multifactorial and many of the underlying mechanisms as well as their clinical significance for high-incidence diseases are not yet fully understood. This review aims to shed light on the impact and mechanisms of CTS on the actions of diverse stem cells and the involvement of CTS in the many processes of stem cell behavior and provide new insights for the application of CTS and stem cell therapy in treating high-incidence diseases.